Tax Avoidance : Faktor-Faktor Yang Mempengaruhinya (Studi Empiris Perusahaan Nonperbankan Go Public yang Masuk penilaian CGPI Tahun 2009-2014) - Tantriana, Tantriana; , Drs. Muhammad Abdul Aris, M.Si (2016)
Tax avoidance is a strategy and technique to avoid paying tax in the realm of tax law. This study aims to examine the the effect of leverage, corporate governance, and executive character to tax avoidance. Population from this study is go public nonbanking companies listed on Corporate Governance Perception Index from 2009 to 2014. The sample was determined by purposive sampling method in order to get a sample size of 47 datas. Data were analized by multiple linear regression. The result of this study indicate that (1) leverage hasn't significant effect to tax avoidance; (2) corporate governance has significant effect to tax avoidance; and (3) executive character has significant effect to tax avoidance. This result were consisten to previous studies of Budiman and Setiyono (2012); Kurniasih and Sari (2013); Prakosa (2014); Darmawan and Sukartha (2014); Dewi and Jati (2014); and Maharani and Suardana (2014).